Live streaming's reigning monarchs: Delving into the pivotal role of influencers through live broadcasts - Erwin, Erwin; Maupa, Haris; Jilbert, Julius; Sanusi, Abdullah; Suade, Yuyun Karystin Meilisa (Jurnal Siasat Bisnis, 2026)
Purpose – The ubiquity of online businesses has seen a surge in influencer marketing, with live streaming emerging as a prominent strategy. However, the pivotal role of influencers, individuals with a substantial social media following, in live streaming and their subsequent influence on customer behavior justifies a thorough investigation. This research digs into the role of influencers in live streaming and examines their impact on Customer Engagement and Brand Awareness through live streaming activities.Design/methodology/approach – A sample of 225 online customers joined this study. Data was collected using a questionnaire using a 5-point Likert scale and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) processed with WarpPLS Version 8.0.Findings – Influencers can substantially contribute to both customer engagement and brand awareness through live streaming. However, the study indicates that influencers do not directly contribute to brand awareness. Influencers reign supreme in the realm of live streaming, showing their potential to enhance customer engagement and brand awareness. The study offers valuable insights for businesses and influencers to effectively leverage live streaming to meet their marketing goals.Research limitations/implications – The cross-sectional design of the study hinders causal inferences. Longitudinal research and broader sampling are necessary to establish temporal relationships and generalize findings to diverse populations and regions.Practical implications – The research suggests that businesses should strategically select influencers, leverage live streaming for engagement and brand, foster authentic relationships, and measure campaign performance while combining influencer marketing with other digital strategies.Originality/value – This research offers a comprehensive exploration of the synergistic relationship between influencers and live streaming in driving customer engagement and brand awareness, providing empirical evidence and practical recommendations for marketers.